2001
DOI: 10.1089/08892220151126607
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD8+T Lymphocyte Subsets with the Most Commonly Used Markers to Monitor HIV Type 1 Infection in Children Treated with Highly Active Antiretroviral Therapy

Abstract: In contrast to adults, there is no information about children concerning the effects of the new antiretroviral therapy on the chronic activation and expansion of CD8+ T cells. We have investigated the relationship between blood CD8(+) T cell subsets, with percent CD4+ cells (%CD4), percent CD8+ cells (%CD8), and plasma viral load (VL), in 39 vertically HIV-1-infected children receiving highly active antiretroviral therapy (HAART) (mean age, 7.6 years; range, 2-15.6 years). CD8+ subsets were examined by three-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
3
8
1
Order By: Relevance
“…Several studies have described the immunologic profile of HIV-positive children but did not include extensive flow cytometry analyses of lymphocyte subsets, using more than 2 fluorochromes, or age-matched healthy controls, as this study has13, 17, 18. We found that the profile of HIV-infected children is characterized by low values for helper T cells and high values for cytotoxic T cells, as well as a reduced naive T-cell population.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies have described the immunologic profile of HIV-positive children but did not include extensive flow cytometry analyses of lymphocyte subsets, using more than 2 fluorochromes, or age-matched healthy controls, as this study has13, 17, 18. We found that the profile of HIV-infected children is characterized by low values for helper T cells and high values for cytotoxic T cells, as well as a reduced naive T-cell population.…”
Section: Discussionmentioning
confidence: 88%
“…The HIV-infected children also had increased values for memory CD8+ T cells. Other studies have shown this to be associated with HIV viremia and decreases in CD4+ T cells 17, 21…”
Section: Discussionmentioning
confidence: 94%
“…Among HIV-infected American and Spanish children, for example, naïve cells constituted 55–56% and 30–38% of the CD4 + and CD8 + T cell populations, respectively, prior to HAART initiation, 33;37;38 while the corresponding percentages in HIV-infected Zambian children constituted only 19% and 4%. These differences are underscored by the older median ages of 7 to 10 years in the American and Spanish cohorts, as older age typically is associated with lower naïve T cell percentages.…”
Section: Discussionmentioning
confidence: 97%
“…10,27 The percentage of CD4 ϩ T cells and CD8 ϩ T cells was calculated with respect to all lymphocytes whereas the percentage of the various subsets was calculated with respect to the corresponding CD4 and CD8 cell numbers. The phenotypic subset analyses were carried out in one centralized facility using a standardized methodology (Laboratorio de Immuno-Biologia Molecular).…”
Section: Tcr Rearrangement Excision Circles Quantificationmentioning
confidence: 99%
“…[4][5][6] The effect of HAART in immune system reconstitution is shown by a consistent increase in CD4 ϩ T cell counts and in thymic function in young HIV-infected patients, 7,8 even in advanced stages of disease. 5,6 HIV infection also induces a lymphoid cell activation resulting in an increase of T cell activation-associated cell surface markers, such as CD38 and HLA-DR. [9][10][11] Those markers change in parallel with the progression of the disease both in adults and children, 9,12 but decrease in response to HAART. 6,13 Moreover the levels of CD8 ϩ CD38 ϩ T cells offer additional and independent predictive values to plasma viral load (VL) 13 and CD4 ϩ T cells assays, 12,14 suggesting that additional factors may be involved in HIV pathogenesis and thus contribute to high levels of CD38 ϩ cells.…”
Section: Introduction H Uman Immunodeficiency Virus Type 1 (Hiv-1) Inmentioning
confidence: 99%